EL PAPEL DE LA ORGANIZACIÓN AUTÓNOMA EN EL CAMBIO CULTURAL: ¿DETERMINADOS O RECONFIGURABLES POR LA ORGANIZACIÓN AUTÓNOMA? - Sobrado Cháves, Miguel Ángel; Rojas Herrera, Juan José (Universidad de Costa Rica, 2020)
The general objective of this article is to reflect on the causes that explain the ancestral backwardness of Latin American societies and provide an exit strategy to this problem. The methodology used consisted of reviewing extensive bibliographic material that shows that the failed state and the submissive and dilettante civil society, which today distinguishes most of the Latin American countries, constitute the two sides of the same vicious circle, which reproduces the economic lag and facilitates the ideological and political manipulation of predatory patronage. In order to face such structural obstacles, it is recommended to undertake a process of change that allows promoting, simultaneously and in coordination, the comprehensive reform of the client state and the autonomous organization of the people, so that when they become a collective subject, they mobilize in favor of building innovative solutions from below.